Modeling, Simulation, and Implementation of Solar‐Driven Water‐Splitting Devices. Issue 42 (6th October 2016) - Xiang, Chengxiang; Weber, Adam Z.; Ardo, Shane; Berger, Alan; Chen, YiKai; Coridan, Robert; Fountaine, Katherine T.; Haussener, Sophia; Hu, Shu; Liu, Rui; Lewis, Nathan S.; Modestino, Miguel A.; et al.
Abstract: An integrated cell for the solar‐driven splitting of water consists of multiple functional components and couples various photoelectrochemical (PEC) processes at different length and time scales. The overall solar‐to‐hydrogen (STH) conversion efficiency of such a system depends on the performance and materials properties of the individual components as well as on the component integration, overall device architecture, and system operating conditions. This Review focuses on the modeling‐ and simulation‐guided development and implementation of solar‐driven water‐splitting prototypes from a holistic viewpoint that explores the various interplays between the components. The underlying physics and interactions at the cell level is are reviewed and discussed, followed by an overview of the use of the cell model to provide target properties of materials and guide the design of a range of traditional and unique device architectures. Abstract : Catching the sun : Significant advances have been made in recent years on the modeling‐ and simulation‐guided development of integrated solar‐driven water‐splitting devices. Multidimensional multiphysics models have provided design guidelines for semiconductors, electrocatalysts, as well as liquid and membrane electrolytes. This Review discusses the guiding principles and key findings of these activities.